Design and experimental analysis of an Integral Collector Storage (ICS) prototype for DHW production. (1st February 2020) - Bilardo, Matteo; Fraisse, Gilles; Pailha, Mickael; Fabrizio, Enrico
Graphical abstract: Highlights: Design of an integral collector storage prototype with phase change material and heat pipes. Experimental campaign in summer and winter condition. Domestic hot water production and overall energy performance assessment. Abstract: This paper presents an innovative solar ICS (Integral Collector Storage) for the production of Domestic Hot Water (DHW). The novelty consists in combining an absorbent surface, heat pipes and a storage cavity made up of a phase change material (PCM) within a single compact casing. The energy performance of the system was experimentally studied in different seasons of the year, with and without domestic hot water production. The temperatures inside the collector were monitored using K-type thermocouples and their trends were analysed and discussed. During the experimental phase, the thermal storage reached the maximum temperature of 79.3 °C, exploiting the latent heat of the PCM. Overall performances demonstrated good agreement with results available in the literature in terms of efficiency and energy storage. A specific heat flux of 2.64 kW·m −2 was achieved in DHW production, with a water flowrate of 0.87 kg·min −1 . The 0.02 m 3 PCM section was able to store 24.57 kWh of thermal energy along a monitored month. Future developments of this new technology include new experimental tests with larger prototypes and the coupling with a real user.